WEB-BASED PHOTOGRAPHY SERVICES RENTAL INFORMATION SYSTEM AT MARS DWI JAYA PHOTO STUDIO - Muhammad Iqbal Alfani; Yulian Findawati; Suprianto Suprianto; Metatia Intan Mauliana (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to develop a web-based application for Mars Dwi Jaya Photo Studio to address the lack of accessible information for consumers and the difficulties encountered in determining service prices. Method: The research follows a system development approach by designing and implementing a website-based application using a MySQL database operated on a localhost server. The system architecture includes modules for service promotion, price management, and online order transactions, allowing administrators to manage content and customers to interact directly with the platform. Results: The developed application successfully facilitates online promotion and rental service transactions, enabling users to access information, compare prices, and make service bookings efficiently without visiting the studio physically. The system also enhances operational efficiency by reducing manual processes in price determination and customer service. Novelty: This study provides an innovative solution for small-scale photo studios by integrating online rental management and interactive customer communication into a single web-based platform, thus supporting the digital transformation of local creative businesses.